2005
DOI: 10.1016/j.plasmid.2004.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Cryptic plasmid pSKU146 from the wall-less plant pathogen Spiroplasma kunkelii encodes an adhesin and components of a type IV translocation-related conjugation system

Abstract: "Cryptic plasmid pSKU146 from the wall-less plant pathogen Spiroplasma kunkelii encodes an adhesin and components of a type IV translocationrelated conjugation system" (2005 AbstractA cryptic plasmid of the wall-less plant pathogenic mollicute, Spiroplasma kunkelii CR2-3X, was cloned and its sequence analyzed. The 14,615 bp plasmid, designated pSKU146, has a nucleotide content of 28 mol% G + C, and contains 18 potential protein-coding regions (open reading frames, ORFs), of which six encode proteins that exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…S4). Clustering of Soj from S. citri pSciA and pSci6 and S. kunkelii pSKU146 with those of the mycoplasmal mobile elements is consistent with previous observations that the arrangement of three CDS of pSKU146 paralleled that of their counterparts in the integrated conjugative element (ICE) of Mycoplasma fermentans (Calcutt et al, 2002;Davis et al, 2005), and suggests that spiroplasma plasmids and mycoplasma ICEs might have a common ancestor. It is noteworthy that, in contrast to spiroplasmas, most mycoplasmas do not possess parA/soj genes (Livny et al, 2007), and that mycoplasmas having parA/soj-like sequences all belong to the 'pneumoniae' phylogenetic group.…”
Section: Partitioning Protein Sojsupporting
confidence: 89%
See 2 more Smart Citations
“…S4). Clustering of Soj from S. citri pSciA and pSci6 and S. kunkelii pSKU146 with those of the mycoplasmal mobile elements is consistent with previous observations that the arrangement of three CDS of pSKU146 paralleled that of their counterparts in the integrated conjugative element (ICE) of Mycoplasma fermentans (Calcutt et al, 2002;Davis et al, 2005), and suggests that spiroplasma plasmids and mycoplasma ICEs might have a common ancestor. It is noteworthy that, in contrast to spiroplasmas, most mycoplasmas do not possess parA/soj genes (Livny et al, 2007), and that mycoplasmas having parA/soj-like sequences all belong to the 'pneumoniae' phylogenetic group.…”
Section: Partitioning Protein Sojsupporting
confidence: 89%
“…In particular, they do not share any homology with the phytoplasma plasmids that encode putative replication proteins (Rep) having the conserved motifs associated with the rolling circle mechanism of replication (Oshima et al, 2001;Tran-Nguyen & Gibb, 2006). S. citri plasmids pSciA and pSci1-6 all possess genes soj and pE, which are also conserved in plasmids pBJS-O from S. citri BR3 (Joshi et al, 2005) and pSKU146 from S. kunkelii CR2-3X (Davis et al, 2005). In this study, we showed that pE is essential and the only plasmid-encoded protein required for plasmid replication.…”
Section: Discussion Replication Protein Pementioning
confidence: 99%
See 1 more Smart Citation
“…73,2009 BIOLOGICAL DIVERSITY OF PROKARYOTIC T4SS 777 processing of conjugative DNA elements, yet most of them still rely on a T4CP to recruit and bind protein substrates. Some T4SS of medical importance, e.g., the Bordetella pertussis Ptl and Brucella sp.…”
Section: Effector Translocator Systemsmentioning
confidence: 99%
“…The outcome of these investigations led to a general model that secretion signals are positioned near the C VOL. 73,2009 BIOLOGICAL DIVERSITY OF PROKARYOTIC T4SS 779 termini and consist of clusters of hydrophobic or positively charged residues. More recent findings, however, suggest that substrate recognition is mediated by a combination of C-terminal signals, additional intrinsic motifs, and other cellular factors, e.g., chaperones and accessory proteins (Table 1).…”
Section: Substrate Recognition Signals Secretion Chaperones and Accmentioning
confidence: 99%